Interferon Production by Human Leukocytes In Vitro: Some Biological Characteristics - Lee, Spencer H. S. (1969)
Interferon was optimally produced in human peripheral leukocyte cultures incubated for approximately 19 hr in the presence of Sendai virus at a multiplicity of 10 to 50 EID(50)/cell. For determining whether deoxyribonucleic acid (DNA) synthesis per se was essential for interferon production, 1-β-D-arabinofuranosylcytosine (Ara-C), a potent DNA inhibitor was studied for its effect on interferon production in leukocytic and bone marrow cell cultures. These cells showed no impaired capacity to produce interferon when treated with 15 μg of Ara-C per ml. Interferon yields were also determined in leukocyte cultures treated with actinomycin D (0.1 μg/ml) and puromycin (10 μg/ml) at various times before and after virus inoculation. The data suggested that sequential transcriptive and translational events were required for the de novo synthesis of interferon by the infected leukocytes, in a manner similar to other known virus-induced interferon-producing systems. The synthesis of macromolecules and the effects of antimetabolites in leukocytes and bone marrow cell cultures were followed by measuring the incorporation of thymidine-2-(14)C, uridine-5-(3)H, and L-phenylalanine-1-(14)C. The effect of 0.1 μg of actinomycin per ml on the capacity of leukemic leukocytes to produce interferon was also studied. Preliminary data showed that, in contrast to nonleukemic leukocytes, interferon production by leukemic leukocytes was only partially inhibited by actinomycin.